Astrovirus infection in animals (literature review) - V. A. Mischenko; A. V. Mischenko; Т. B. Nikeshina; О. N. Petrova (Ветеринария сегодня)
Viral agents are a major cause of mass gastroenteritides in newborn calves in the countries around the world. Early postnatal diarrhea as the main reason of morbidity and mortality in young animals leads to serious problems in the commercial livestock farming and causes a considerable economic damage. The most common viral gastroenteritis agents in calves are rotaviruses, coronaviruses and pestiviruses, and, along with these, astroviruses are increasingly being detected. The members of the family Astroviridae can cause various pathologies in animals: enteritis, hepatitis and nephritis in birds, gastroenteritis, neurological syndromes and encephalitis in mammals. The role of these viruses in the etiology of respiratory pathology in animals has been demonstrated. The following animals are the natural hosts of astrovirus: cattle, small ruminants, camels, deer, yaks, roe deer, buffaloes, alpacas, pigs, wild boars. The virus has been detected in bats, rodents and marine mammals, as well as in mollusks. Presently, the list of animals susceptible to astrovirus infection has expanded to over 80 species from 22 families, including domestic, synanthropic and wild animals, birds and mammals living in the terrestrial and aquatic environments. In recent times, there has been a lot of evidence of occurrence of recombinant astrovirus isolates, which contributes to the emergence of new genetic variants of the pathogen. A wide variety of infected animal species, the genetic diversity of the virus and the recombination events are indicative either of the cross-species transmission and subsequent adaptation of the virus to new hosts, or of the coinfection of the same host with different virus genotypes, which may lead to the emergence of novel astroviruses that are capable of infecting animals or possess a zoonotic potential. Astrovirus infection has no specific clinical features that allow for its differentiation from other intestinal infections. The presented data highlight the necessity for taking into account astrovirus infection when testing pathological material samples from diarrhea-affected newborn calves, lambs, goat kids and piglets on the commercial farms of the country.